Reviewing the implementation of the accounting information system (SIA) for Bank Indonesia Services to optimize MSME digitalization program in Tolitoli Regency as an Affirmation Area - Syahputra, Rendy Aziz; Sujai, Muhammad; Aqfir, Aqfir (International Journal of Applied Finance and Business Studies, 2025)
This study analyzes the effectiveness of the Financial Information Recording Application Information System (SIAPIK) in supporting environmentally friendly Micro, Small, and Medium Enterprises (MSMEs) in Tolitoli Regency, Central Sulawesi. The objective is to evaluate SIAPIK’s role in improving financial records, operational efficiency, and business decision-making, as well as its impact on marketing, access to capital, and business growth. The research employed a mixed-method approach, combining quantitative surveys and qualitative in-depth interviews with 24 MSMEs actively using SIAPIK (out of 106 surveyed). The results indicate that 83% of respondents reported improved recording efficiency, 79% found financial statements easier to understand, 71% experienced sales growth of up to 15%, and 67% successfully accessed cooperative or banking financing using SIAPIK reports. Nevertheless, 58% still faced challenges such as limited internet access and low digital literacy. Overall, SIAPIK has made a positive contribution to the digital transformation of MSMEs in affirmation areas, particularly in the culinary sector, while emphasizing the need for infrastructure development, continuous training, and cross-sector collaboration. The novelty of this research lies in its focus on environmentally friendly MSMEs in rural 3T regions, which are still underrepresented in the literature on MSME digitization in Indonesia.